2020
DOI: 10.1177/0194599820951175
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of Second Primary Oropharyngeal Cancers in Patients With p16+ Oropharyngeal Cancer

Abstract: Objective To systematically review the literature to determine the prevalence and clinical outcomes of second primary oropharyngeal squamous cell carcinoma (OPSCC). Data Sources Search strategies created with a medical librarian were implemented using multiple databases in October 2019. Review Methods The population of interest included adults age >18 years with a p16+ or human papillomavirus-positive OPSCC. The outcome was a synchronous or metachronous second primary OPSCC. Inclusion and exclusion criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
1
4
0
Order By: Relevance
“…According to HPV status and the overall risk of SPC, we found a significantly lower risk of SPC in patients with HPV+ OPSCC index tumours. Other studies also found a lower risk of SPC in patients with p16+ OPSCC [ 22 , 32 ] but did not use double positivity for both HPV DNA and p16, as in this study. Based on the same database, Grønhøj, C. et al [ 34 ] established earlier that HPV+ patients are less likely to have both distant- ( p = 0.02) and loco-regional ( p = 0.001) recurrence following OPSCC.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…According to HPV status and the overall risk of SPC, we found a significantly lower risk of SPC in patients with HPV+ OPSCC index tumours. Other studies also found a lower risk of SPC in patients with p16+ OPSCC [ 22 , 32 ] but did not use double positivity for both HPV DNA and p16, as in this study. Based on the same database, Grønhøj, C. et al [ 34 ] established earlier that HPV+ patients are less likely to have both distant- ( p = 0.02) and loco-regional ( p = 0.001) recurrence following OPSCC.…”
Section: Discussionsupporting
confidence: 48%
“…Alcohol consumption and tobacco smoking are notable risk factors for developing SPC, especially regarding cancers localized in the upper aerodigestive tract, lungs, and oesophagus [ 21 ]. Studies have shown that p16+ OPSCCs have lower risk of SPC [ 22 ], primarily driven by a decrease in SPCs within the upper aerodigestive tract [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, if patients with tonsil primaries are treated with definitive radiation, and perhaps even adjuvant radiation, it is plausible that the base of tongue receives a dose of radiation adequate enough to treat a small subclinical SPM of the tongue base, while the contralateral tonsil does not. Additionally, multiple studies have included only patients with tonsil primaries, 25–27 while others lack specific subsite information on the site of the index tumor 4 …”
Section: Discussionmentioning
confidence: 99%
“…This was not associated with improved OS in this cohort. TORS has been shown to be safely and effectively utilized in the recurrent setting as well as in second primary oropharyngeal malignancies 25,32 . Additionally, as a single modality, surgery provides the advantage of a one‐time treatment versus repeated daily treatments over several weeks.…”
Section: Discussionmentioning
confidence: 99%
“…TORS has been shown to be safely and effectively utilized in the recurrent setting as well as in second primary oropharyngeal malignancies. 25,32 Additionally, as a single modality, surgery provides the advantage of a one-time treatment versus repeated daily treatments over several weeks. The acute toxicity of radiation therapy is well described in the literature, which can lead to interruptions or early discontinuation of treatment.…”
Section: Discussionmentioning
confidence: 99%